Temperature Reduction Performance of Radiative Cooling Paint on Building Roofs - Hakim, Muhammad Fuad Abdul; Putra, Mohammad Alexin; Subekti, Fajar (TURBO [Tulisan Riset Berbasis Online], 2025)
Passive cooling technologies continue to be developed to provide a cooling effect without external energy input. One example is radiative cooling paint (RCP). RCP dissipates heat by emitting thermal radiation and reflecting solar irradiation, thereby reducing the temperature of the coated object. The temperature reduction performance of RCP is influenced by the substrate on which it is applied. Previous studies have generally not included substrates with potential applications for RCP, such as building roofs. This study aimed to evaluate the temperature reduction performance of RCP when applied to different roofing materials. RCP samples were prepared using barium sulfate pigment and applied to corrugated metal roofing, clay roof tiles, and stone-coated metal roofing, then tested under direct sunlight. The results showed that applying RCP reduced the average temperature by 6 °C (13.1%) on corrugated metal roofing, 6.4 °C (13.3%) on clay roof tiles, and 14.1 °C (24.7%) on stone-coated metal roofing.